Seletividade de herbicidas para a cultura do grão-de-bico - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
Chickpea (Cicer arietinum L.) is an important legume grown in the world with high productive, economic and nutritional potential. In Brazil, chickpea consumption is still limited, in spite of the increasing demand in the country, due to the excellent nutritional characteristics of the grains. To contribute to the expansion and consequent consolidation of chickpeas as an alternative to the crop rotation system, it is crucial the availability of information that guides farmers in the field. Thus, in the chickpea crops, weeds are the main agronomic challenge. As a result, the use of herbicides is the leading and most efficient tool used for their control. However, in Brazil, there are still no registered herbicides for chickpea crops. Then, the objectives of this work were to evaluate the selectivity of herbicides sprayed before and after emergence for chickpea crops. For this, four experiments were developed, two in the greenhouse and the other two in the field in the municipality of Urutaí, Goiás State, in the 2015/2016 agricultural year. In each greenhouse experiment, eight herbicides were applied in two doses. The treatments selected for the experiment under field conditions were based on the results obtained in the greenhouse experiments. The herbicides clomazone, diclosulam, flumioxazin, metribuzin, and trifluralin sprayed in pre-emergence and the herbicides bentazon, chlorimuron-ethyl, and imazethapyr applied in the post-emergence were not considered selective for the chickpea culture, in the greenhouse experiments, for both dosages. Based on the results obtained in the greenhouse and field experiments, it was concluded that the herbicides pendimenthalin, s-metolachlor, and sulfentrazone in both dosages applied in pre-emergence and the herbicides clethodim, fluazifop-p-butyl, fomesafen, haloxyfop -methyl and lactofen applied in post-emergence, both dosages, were considered selective for the chickpea culture.
Keywords: Controle químico; Fitointoxicação; Cicer arietinum L.; Hortaliça; Leguminosa; Plantas daninhas; Chemical control; Phytotoxification; Cicer arietinum L.; Vegetables; Leguminous; Weeds; CIENCIAS AGRARIAS